Cerdas Mengelola Uang, Cerdas Berbisnis: Literasi Keuangan dan Dampaknya pada Wirausaha Muda - Rahmawati, Wahyuni; Nazwa, Naila (Undergraduate Program in Accounting, Department of Accounting, Faculty of Economics and Business, Universitas Tanjungpura, 2026)
This study aims to examine the effects of financial literacy and financial training on financial inclusion among student entrepreneurs at Pamulang University in 2025. This research employs a quantitative approach with a causal associative design. Primary data were collected from 100 respondents through a structured questionnaire using a five-point Likert scale. The respondents were active students who were involved in entrepreneurial activities. Data were analyzed using multiple linear regression, supported by validity, reliability, and classical assumption tests. The results show that financial literacy has a positive and significant effect on financial inclusion, with a regression coefficient of 0.339, a t-value of 3.995, and a significance value of less than 0.001. Financial training also has a positive and significant effect on financial inclusion, with a regression coefficient of 0.597, a t-value of 6.545, and a significance value of less than 0.001. Simultaneously, financial literacy and financial training significantly affect financial inclusion, with an adjusted coefficient of determination of 77.8%. These findings indicate that mastery of basic financial concepts, when strengthened through practical financial training, can increase student entrepreneurs’ participation in formal financial services and support the use of banking products, financing mechanisms, and digital financial platforms in business activities.